Alte und neue Medialität an der Schwelle zur digitalen Wende : das mediale Echo Thomas Bernhards und die Selbstinszenierung Elfriede Jelineks - Zdeněk Pecka (Brünner Beiträge zur Germanistik und Nordistik, 2019)
The Austrian authors Thomas Bernhard and Elfriede Jelinek established themselves as personalities whose radicalism, provocations and public gestures became part of the impact of their work. It can be seen that the radical reflections of the narrators and characters are a statement continuation of the authors. At Bernhard, the ways which communicate this self-staging are still "old" (press and television). Jelinek exclusively uses the "new" medium Internet and the website already set up at the beginning of the digital turn for her self-presentation and publication.